Early Childhood Curiosity in Books “Kau Sedang Apa, Lala?” By Widya Ross - Widhyastuti, Ari (International Proceedings of Nusantara Raya, 2024)
This research aims to describe the value of character education contained in the book '"What are you doing, Lala?" Widya Ross's work. This research is a qualitative descriptive research with a literature study approach. The data collection techniques used are documentation and literature study. The data analysis used is a qualitative content analysis technique. The research results showed that several character values ​​were found in the book. In the book "What are you doing, Lala?" Widya Ross's work found 3 character education values, namely creative character, caring and curiosity. The conclusion is in the book “What are you doing, Lala? Widya Ross's work has the most dominant value of character education, namely the character education of curiosity. The message of this story is about the importance of curiosity in early childhood. The message of this story is to be creative in doing things, care about the situation and communicate curiosity politely and politely.